Youtuus, a new bamboo-feeding genus of the tribe Augilini with two new species from China (Hemiptera, Fulgoromorpha, Caliscelidae) - Gong, Nian (Zookeys, 2018)
Abstract. A new bamboo-feeding planthopper genus Youtuus Chen & Gong, gen. n. with two new species Y.erythrus Gong, Yang & Chen, sp. n. and Y.strigatus Gong, Yang & Chen, sp. n. (Hemiptera: Fulgoromorpha: Caliscelidae: Ommatidiotinae: Augilini), are described and illustrated from China. Keys to the genera of Augilini and the species of Youtuus Chen & Gong, gen. n. are given.